Identification of native and non-native grass shrimps Palaemon spp. (Decapoda: Palaemonidae) by citizen science monitoring programs in Atlantic Canada. Issue 2 (15th February 2019) - Pearson, Jessie M N; Kidd, Jess A; Knysh, Kyle M; Van den Heuvel, Michael R; Gagnon, Jean-Marc; Courtenay, Simon C
Abstract: Grass shrimp collected by the Community Aquatic Monitoring Program (CAMP) in estuaries of the southern Gulf of St. Lawrence, Canada were previously assumed to be the native Palaemon vulgaris Say, 1818 . Taxonomic identification of grass shrimps from CAMP estuaries revealed most individuals were P. vulgaris, but several from the Souris River and Trout River estuaries in Prince Edward Island (PEI) belong to the European species P. adspersus Rathke, 1837 . We provide the first documented presence of P. adspersus in PEI estuaries, extending its known range in Atlantic Canada from coastal Newfoundland and the Magdalen Islands. Boat traffic was probably responsible for the introduction of P. adspersus . The results highlight the importance of community-based monitoring in coastal ecology.